Megakaryocyte and Platelet Transcriptomics for Discoveries in Human Health and Disease. Issue 6 (June 2020) - Davizon-Castillo, Pavel; Rowley, Jesse W.; Rondina, Matthew T.
Abstract : Anucleate platelets, long viewed as merely cell fragments with a limited repertoire of rapid-acting hemostatic functions, are now recognized to have a complex and dynamic transcriptome mirroring that of many nucleated cells. The field of megakaryocyte and platelet transcriptomics has been rapidly growing, particularly with the advent of newer technologies such as next-generation RNA-sequencing. Studies interrogating the megakaryocyte and platelet transcriptome have led to a number of key insights into human health and disease. In this brief focused review, we will discuss some of the recent discoveries made through transcriptome analysis of megakaryocytes and platelets. We will also highlight the utility of integrating ribosome footprint analysis to augment discoveries. Both bulk and single-cell sequencing approaches will be reviewed, along with comparative studies between human and murine platelets under basal healthy settings and during acute systemic inflammatory diseases.